Optical characterization of europium-doped indium hydroxide nanocubes obtained by Microwave-Assisted Hydrothermal method - Motta, Fabiana Villela Da; Marques, Ana Paula De Azevedo; Araújo, Vinícius Dantas De; Tavares, Mara Tatiane De Souza; Delmonte, Mauricio Roberto Bomio; Paskocimas, Carlos Alberto; Li, Máximo Siu; Nascimento, Rubens Maribondo Do; Longo, Elson [UNESP] (ABM, ABC, ABPol, 2014)
Crystalline europium-doped indium hydroxide (In(OH)3:Eu) nanostructures were prepared by rapid and efficient Microwave-Assisted Hydrothermal (MAH) method. Nanostructures were obtained at low temperature. FE-SEM images confirm that these samples are composed of 3D nanostructures. XRD, optical diffuse reflectance and photoluminescence (PL) measurements were used to characterize the products. Emission spectra of europium-doped indium hydroxide (IH:xEu) samples under excitation (350.7 nm) presented broad band emission regarding the indium hydroxide (IH) matrix and 5D0 → 7F0, 5D0 → 7F1, 5D0 → 7F2, 5D0 → 7F3 and 5D0 → 7F4 europium transitions at 582, 596, 618, 653 and 701 nm, respectively. Relative intensities of Eu3+ emissions increased as the concentration of this ion increased from 0, 1, 2, 4 and 8 mol %, of Eu3+, but the luminescence is drastically quenched for the IH matrix.
Keywords: Indium hydroxide; Europium; Microwave-Assisted Hydrothermal; Nanostructures